Beer sales in grocery and convenience stores: a glass half-full for craft brewers? - Palardy, Nathan, author; Costanigro, Marco, author; Cannon, Joseph, author; Thilmany, Dawn, author; Berning, Joshua, author; Bayham, Jude, author; Callaway, Jeff, author; Informa UK Limited, publisher (Colorado State University. Libraries, 2023)
We study how regulatory changes influence the market dynamics underlying business location decisions by investigating how a 2019 law introducing full-strength beer into grocery and convenience stores in the US state of Colorado impacted craft brewers a year after implementation. A state-wide survey reveals that the new channels brought limited change to how craft breweries sell beer. Access to grocery stores advantages larger craft breweries, while smaller breweries face significant logistical barriers. Analysis of mobile phone geolocation data reveals a modest reduction in visitation to liquor stores. Results suggest that the policy change will not impair Colorado's ability to draw craft beer investment.
Keywords: alcohol distribution laws; policy evaluation; three-tier system; store traffic; interrupted time-series analysis; state-space forecasting